2015
DOI: 10.1371/journal.pone.0132702
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA Double-Strand Breaks and Cytotoxicity after 7 Tesla Magnetic Resonance Imaging of Isolated Human Lymphocytes

Abstract: The global use of magnetic resonance imaging (MRI) is constantly growing and the field strengths increasing. Yet, only little data about harmful biological effects caused by MRI exposure are available and published research analyzing the impact of MRI on DNA integrity reported controversial results. This in vitro study aimed to investigate the genotoxic and cytotoxic potential of 7 T ultra-high-field MRI on isolated human peripheral blood mononuclear cells. Hence, unstimulated mononuclear blood cells were expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 38 publications
(51 reference statements)
0
25
0
1
Order By: Relevance
“…Three of the studies showed no enhancement of DSB following either in vitro exposure of human cancer cell lines 0, 1, or 24 h post exposure, 18 in vitro exposure of human lymphocytes 0, 1, or 20 h post exposure, 23 or in human lymphocytes taken 5 min after in vivo exposure of patients undergoing contrast-enhanced cardiac magnetic resonance imaging (CMR). 22 In contrast, Fiechter et al 8 reported a statistically significant enhancement in DSB in human lymphocytes taken from patients immediately following contrast-enhanced CMR.…”
Section: Does Mri Exposure Lead To Dna Damage?mentioning
confidence: 99%
“…Three of the studies showed no enhancement of DSB following either in vitro exposure of human cancer cell lines 0, 1, or 24 h post exposure, 18 in vitro exposure of human lymphocytes 0, 1, or 20 h post exposure, 23 or in human lymphocytes taken 5 min after in vivo exposure of patients undergoing contrast-enhanced cardiac magnetic resonance imaging (CMR). 22 In contrast, Fiechter et al 8 reported a statistically significant enhancement in DSB in human lymphocytes taken from patients immediately following contrast-enhanced CMR.…”
Section: Does Mri Exposure Lead To Dna Damage?mentioning
confidence: 99%
“…The platform, named AKLIDES (Medipan, Dahlewitz, Germany), permits a fully automated assessment of antinuclear immunofluorescence antibody screening (12), but also allows computational analysis of γ-H2AX foci, which has now been successfully validated by several independent research groups (13)(14)(15)(16)(17). The suitability of the γH2AX assay to evaluate the dose-dependent formation of DSB has also been recently demonstrated for X-ray radiation and 7 Tesla magnetic resonance image exposure (17)(18)(19)(20). Therefore, the aim of the present study was to investigate the potential genotoxic effect of mobile phone RF exposure on human peripheral blood mononuclear cells (PBMCs) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In the other studies, various combinations of clinical MRI sequences were used. In some cases, the sequences were only mentioned by name [Simi et al, 2008;Lee et al, 2011;Szerencsi et al, 2013;Critchley et al, 2018], and in other cases, they were described with more details about the specific settings used [Schwenzer et al, 2007a,b;Reddig et al, 2015;Fatahi et al, 2016;Friebe et al, 2018].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Four studies gave no specifics about the gradient fields involved [Simi et al, 2008;Lee et al, 2011;Szerencsi et al, 2013;Critchley et al, 2018], making the exposure conditions impossible to replicate. The remaining four studies [Schwenzer et al, 2007a,b;Reddig et al, 2015;Fatahi et al, 2016;Friebe et al, 2018] provided peak gradient field strengths and peak slew rates, which could be useful information together with the exact position of the sample. Unfortunately, the position of the sample was either not given [Schwenzer et al, 2007a] or not specific [Reddig et al, 2015;Fatahi et al, 2016;Friebe et al, 2018].…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation